Early experience with uniportal robotic thoracic surgery lobectomy - Mercadante, Edoardo; Martucci, Nicola; De Luca, Giuseppe; La Rocca, Antonello; La Manna, Carmine (Frontiers in Surgery, 2022)
Background Invasiveness is considered one of the cornerstones of every field of surgery, and video-assisted thoracoscopic (VATS) approaches are now routinely used worldwide to perform pulmonary resections. Recently, robotic-assisted thoracic surgery (RATS) has become the preferred technique in many centers; it is routinely performed using three or four ports with at least one service incision, contrasting with the real concept of invasiveness, especially when compared to uniportal VATS (U-VATS). Hereby, we present our early experience with uniportal RATS (U-RATS) pulmonary resections for early-stage lung cancer. Technical details of surgical steps are accurately described and commented on. Results Twenty-four consecutive patients with lung cancer underwent U-RATS anatomical pulmonary resections at our institute. All procedures were completed with the uniportal approach. The mean operative time was 210 min (range 120–350); in the last 10 cases, the operative time was significantly reduced (180 min) compared to the first 10 cases (232 min) (p < 0.02), showing a very fast learning curve. The postoperative pain score was comparable to that for U-VATS and was constantly low. Conclusions U-RATS is a safe and feasible technique, combining the advantages of U-VATS with the well-known advantages of robotic surgery.